Rigid segments of condensation polyetherurethanes - Białkowska, A.; Wirpsza, Z. (Polimery, 2022)
On the basis of the changes of physical properties such as refractive index, dynamic viscosity, pH value (Table 1) and spectrum analysis (IR, H-1 NMR and C-13 NMR - Figs. 1-5) a probable reaction course (scheme A) and chemical structures of the products formed in the system consisting from urea (here: M), phenylsulfonic acid (K) and formaldehyde (F), have been determined. The products were denoted as MKF111 and MKF112 dependently on the reacting sunstances molar ratios: 1:1:1 and 1:1:2, respectively. The reasons of very limited optimal time of MKF application, guaranting the obtaining of ionomeri polyoxybutyleneurethaneureas (JPURK) with good functional quality, have been explained. There was stated that to obtain JPURK with good set of properties the presence of free sulfonic groups in MKF is a necessary condition.